Dampak penambahan kromium, zink, dan minyak ikan lemuru terhadap saluran pencernaan dan organ dalam ayam IPB D1 - G. S. Afifah; C. Sumantri; R. Afnan; A. S. Harahap; Sumiati (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2025)
The increasing demand for chicken meat in Indonesia has encouraged the development of superior localchickens such as IPB D1, which have the ability to utilize local feed and exhibit rapid growth. Thisstudy aimed to determine the role of zinc, chromium, and lemuru oil supplementation on the digestivesystem development and internal organs functionality of IPB D1 chickens. A total of 100 twelve-weekold IPB D1 chickens were assigned to four treatment groups: control (P0), feed supplemented withzinc and chromium (P1), feed supplemented with lemuru oil (P2), and feed supplemented with zinc,chromium, and lemuru oil (P3). A Completely Randomized Design (CRD) was applied, and significantdifferences were analyzed using Tukey’s post hoc test. The findings revealed no significant impact ofsupplementation on the relative length of the digestive tract. Nonetheless, a significant increase in thepercentage of gallbladder weight was observed in the P3 group (0.09%–0.13%). In contrast, the heartweight percentage was significantly reduced compared to the control group (0.48%–0.58%). Theseresults indicate that combined supplementation of zinc, chromium, and lemuru oil may modulate lipidmetabolism and cardiovascular function in IPB D1 chickens. Further investigations are required toestablish optimal dosages and assess the long-term implications on the performance of IPB D1 chickens.